2021
DOI: 10.18036/estubtdc.714841
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Di̇crocoeli̇i̇dae (Di̇genea) Larval Stages in the First Intermediate Host Helix Lucorum, 1758 in Eskisehir and Bartin Provinces of Turkey

Abstract: This study was conducted to determine the prevalence of Dicrocoeliidae larval stages in Helix lucorum found in Eskişehir and Bartın provinces of Turkey. Snails were collected from the pastures of Eskişehir and Bartın. The snails were anesthetised with 50 mM sterilized magnesium chloride (MgCl2) before dissected. Internal organs of the snail, specifically hepatopancreas, were analysed with a stereomicroscope for sporocyst and cercaria. The larval forms were identified and monitored with a light microscope. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Dicrocoeliid trematodes (DTs) are parasitic organisms of amphibians, reptiles, and mammals, including humans, and land snails are the first intermediate host for DTs [13,14]. Previous prevalence studies conducted in Turkey showed that the infection rates of the larval stages of DTs in H. lucorum were 4.6%, 7%, 4.9%, and 22% in Eskisehir, Bartin, Afyonkarahisar, and Van, respectively [24][25][26]. In the presented study, the infection rate with the larval stages of DT was found to be 20% in Bitlis, Turkey (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dicrocoeliid trematodes (DTs) are parasitic organisms of amphibians, reptiles, and mammals, including humans, and land snails are the first intermediate host for DTs [13,14]. Previous prevalence studies conducted in Turkey showed that the infection rates of the larval stages of DTs in H. lucorum were 4.6%, 7%, 4.9%, and 22% in Eskisehir, Bartin, Afyonkarahisar, and Van, respectively [24][25][26]. In the presented study, the infection rate with the larval stages of DT was found to be 20% in Bitlis, Turkey (Fig.…”
Section: Discussionmentioning
confidence: 99%